La interrelación entre el "capital humano" y el "capital social": Una aproximación al caso espa\~nol - Matías Membiela-Pollán; José Atilano Pena-López; Eva Sánchez-Amboage (Atlantic Review of Economics (ARoEc), 2019)
– The aim of this article is to analyze the bidirectional link between two key variables in economic development and social sustainability: human capital and social capital. After introducing both concepts, the influence of human capital (education, technical knowledge, experience of the individual-worker) in the individual social capital (network of interpersonal relationships of the focal subject) is approached from the theoretical point of view. In this sense, education extends the social network of the individual and broadens the set of resources that can be accessed. Likewise, and in the opposite direction, individual social capital favors both the education of the subject and the productivity of its human capital. The second part of the article contrasts from an empirical point of view the interrelation between human capital and individual social capital in the Spanish case. The results confirm the bidirectionality of the relationships and the need to deepen the causality of the processes.
Keywords: 330; human capital; social capital; education; social network; sustainability